Analysis of Islamic Religious Education in the Face of Liberalism in the Global Era : (Analisis Pendidikan Agama Islam dalam Menghadapi Liberalisme di Era Global) - Dodoh Siti Saadah; Syahidin (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2026)
The development of the times in the global era provides opportunities and challenges for Islamic religious education. One of the challenges is the entry of liberalism. The purpose of this research is to provide an understanding of the entry of liberalism as a result of global openness to Islamic religious education and efforts to minimize the negative impact of liberalism. The research method used is a qualitative approach to the literature study method, with data analysis techniques including the stage: data reduction, data presentation, and verification as well as drawing conclusions. Results obtained: 1) Liberalism in Islamic education should be linked to transcendental relations as the foundation and limitation of liberal action itself; 2) Liberalism has a positive impact that is momentary and a negative impact that is long-term; 3) Efforts that need to be made to minimize the negative impact of liberalism in Islamic education are the need for strategies and policies that are relevant to the needs and adjusted to the philosophical and sociological foundations of Indonesian society. Implications: the findings show the need for an affirmation between liberalism and the transcendental foundation in Islamic education and the urgency of awareness of the dualistic impact of liberalism. Conclusion: liberalism in Islamic education must be limited considering the impact it causes, so that policies that are in accordance with the needs based on the philosophical and sociological needs of the Indonesian nation are needed.